The Role of Education in Building Student Character - Fahmi, Farizan (Global Education Journal, 2025)
Education has a strategic role in shaping the character of students as the nation's future generation (Ministry of Education and Culture of the Republic of Indonesia, 2017). This article aims to analyze the role of education in building student character and identify effective implementation strategies. The method used is library research by analyzing various literature related to character education. The results show that character education not only focuses on cognitive aspects but also instills moral, ethical, and social values that become the foundation of personality. The main components in character formation include the role of teachers as role models, conducive school environment, curriculum integration, and involvement of parents and community. Characters such as honesty, responsibility, discipline, tolerance, and social care must be instilled from an early age through integrated learning. Character education provides significant benefits in forming positive personality, improving learning quality, preparing social life, fostering responsibility and independence, preventing negative behavior, and forming a generation of integrity. Effective implementation strategies include integration in learning, exemplary and habituation, school culture development, stakeholder involvement, and continuous evaluation. In conclusion, education functions as the main foundation in creating a generation with character, integrity, and ready to face life challenges in the global era.